In-hospital mortality of cardiogenic shock complicating ST-elevation myocardial infarction in Malaysia: a retrospective analysis of the Malaysian National Cardiovascular Database (NCVD) registry - Venkatason, Padmaa; Zubairi, Yong Zulina; Wan Ahmad, Wan Azman; Hafidz, Muhammad Imran Abdul; Ismail, Muhammad Dzafir; Hadi, Mohd Firdaus; Zuhdi, Ahmad Syadi Mahmood (BMJ Publishing Group, 2019)
Objectives Cardiogenic shock (CS) complicating ST-elevation myocardial infarction (STEMI) carries an extremely high mortality. The clinical pattern of this life threatening complication has never been described in Malaysian setting. This study is to investigate the incidence, clinical characteristics and outcome of STEMI patients with CS in our population. Design A retrospective analysis of STEMI patients from 18 hospitals across Malaysia contributing to the Malaysian National Cardiovascular Database-acute coronary syndrome) registry (NCVD-ACS) year 2006-2013. Participants 16 517 patients diagnosed of STEMI from 18 hospitals in Malaysia from the year 2006 to 2013. Primary outcome measures In-hospital and 30 day post-discharge mortality. Results CS complicates 10.6% of all STEMIs in this study. They had unfavourable premorbid conditions and poor outcomes. The in-hospital mortality rate was 34.1% which translates into a 7.14 times mortality risk increment compared with STEMI without CS. Intravenous thrombolysis remained as the main urgent reperfusion modality. Percutaneous coronary interventions (PCI) in CS conferred a 40% risk reduction over non-invasive therapy but were only done in 33.6% of cases. Age over 65, diabetes mellitus, hypertension, chronic lung and kidney disease conferred higher risk of mortality. Conclusion Mortality rates of CS complicating STEMI in Malaysia are high. In-hospital PCI confers a 40% mortality risk reduction but the rate of PCI among our patients with CS complicating STEMI is still low. Efforts are being made to increase access to invasive therapy for these patients. © 2019 Author(s) (or their employer(s)). Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.